Microzooplankton Distribution and Dynamics in the Eastern Fram Strait and the Arctic Ocean in May and August 2014 - Lavrentyev, Peter J.; Franzè, Gayantonia; Moore, Francisco B. (Frontiers in Marine Science, 2019)
Microzooplankton community structure, distribution, growth and herbivory were examined in the eastern Fram Strait and Arctic Ocean shelf affected by the Atlantic water inflow in May (during the spring bloom, chlorophyll up to 9 µg l-1) and August (post-bloom, 0.13 – 1.7 µg l-1) 2014. Microzooplankton were collected along two longitudinal transects at 79°N and 79.4 °N from the slope to the ice edge and crossed the Western Spitsbergen Current (WSC). In May, integrated microzooplankton biomass in the upper 100 m ranged from 0.16 g C m-2 above the slope to 2.3 g C m-2 within WSC (0.71 g C m-2 on average). Mixotrophic oligotrich ciliates from the genus Strombidium dominated in the spring and formed a surface bloom (79 x 103 cells L-1, 206 µg C L-1). This is the largest microzooplankton biomass recorded in the Arctic so far. The heterotrophic dinoflagellates Gyrodinium and Protoperidinium were abundant at the diatom-dominated stations in the marginal ice zone. In the summer, a more diverse community included a large proportion of heterotrophic and mixotrophic dinoflagellates, tintinnids, and other ciliates. Microzooplankton biomass increased to the average of 1.27 g C m-2. At the ice-covered and open water stations in the Yermak shelf and deep basin, microzooplankton grew at 0.04 to 0.38 d-1; their species-specific growth rates were up to 1.79 d-1. Microzooplankton herbivory on average removed 72% (36 to >100%) of daily primary production with the exception of Phaeocystis pouchetii colonies. These results indicate that the microbial food web plays a central role in the carbon cycle in this Atlantic-influenced polar system.